2004
DOI: 10.1002/bip.10598
|View full text |Cite
|
Sign up to set email alerts
|

Structural similarity of E. coli 5S rRNA in solution and within the ribosome

Abstract: The article presents translational and rotational diffusion coefficients of 5S rRNA determined experimentally by the method of dynamic light scattering (DLS) and its comparison with the values predicted for different models of this molecule. The tertiary structure of free 5S rRNA was proposed on the basis of the atomic structures of the 5S rRNA from E. coli and H. marismortui extracted from the ribosome. A comparison of the values of DT, tauR, and Rg predicted for different models with experimental results for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Several structural domains of 5S rRNA have been crystallized32 and X‐ray scattering studies in solution have determined that free 5S rRNA is elongated in the absence of bound proteins but becomes more compact when it is in the ribosome33,34 (Figure 4). NMR studies performed on Xenopus laevis 5S rRNA have also shown that while loop E is fully folded in the absence of protein (approximating an A‐formed helix), the junction of helix V and loop A is conformationally heterogenous in the free molecule 1.…”
Section: Introductionmentioning
confidence: 99%
“…Several structural domains of 5S rRNA have been crystallized32 and X‐ray scattering studies in solution have determined that free 5S rRNA is elongated in the absence of bound proteins but becomes more compact when it is in the ribosome33,34 (Figure 4). NMR studies performed on Xenopus laevis 5S rRNA have also shown that while loop E is fully folded in the absence of protein (approximating an A‐formed helix), the junction of helix V and loop A is conformationally heterogenous in the free molecule 1.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a bead-and-spring model of 5S rRNA of E. Coli (PDB code IC2X:C) was built according to the structure sketched in Fig. 1 b [ 20 ]. Again, after equilibrating the initial conformation, BD simulations with and without HI were performed.…”
Section: Resultsmentioning
confidence: 99%
“…a Sketch of the secondary structure of yeast tRNA phe [ 45 ] (note the presence of four helices, three loops and a hinge). b Sketch of the secondary structure of the 5S rRNA [ 20 ] (note the presence of five double helices, four loops, and a hinge). In each case nucleotides are the black points, double helices are the regions with connections between opposite nucleotides and loops are the “circular” regions without connections between opposite nucleotides …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations